Securing Cloud Computing Using - Ahmed Shaker Saidah (2014)
Abstract
Contents
Thesis (M.A.)$1 (BNile University, Egypt, 2014 .s
"Includes bibliographical references"
Text in English, abstracts in English.
Keywords: Information Security; Dissertation, Academic